Sustainable Green Charcoal Briquette from Food Waste via Microwave Pyrolysis Technique: Influence of Type and Concentration of Binders on Chemical and Physical Characteristics - Siti Shawalliah Idris; Muhammad Izwadi Zailan; Nabihah Azron; Norazah Abd Rahman (International Journal of Renewable Energy Development, 2021)
Turning the food waste into a fuel source such as charcoal briquette was one of the alternatives in managing the food wastes disposal. In this present work, food waste was converted into charcoal by microwave irradiation technique. Application of binders such as potato starch and carboxymethyl cellulose (CMC) at ratios of 5%,10% and 15% for briquetting purpose were investigated in terms of its chemical and physical characteristics. Result showed that the briquette formed using the starch as the binder performed better in combustion quality than that of carboxymethylcellulose (CMC). A good quality of charcoal briquette has capability to withstand impact during packaging, handling, and transportation. Standard physical characteristic that was tested for briquette includes moisture content, compressive strength, and impact resistance. Calorific value of briquette was studied to analyse energy content in the briquette. The study showed that food waste charcoal has calorific value comparable to that of the commercial charcoal. However, the addition of binders showed some reduction in the energy content, with more reduction when CMC is added. In terms of combustion characteristic, the addition of binders does not alter the combustion profile in comparison to the raw food waste charcoal’s profile. The ignition and burnout temperatures of the food waste charcoal briquette showed a better performance with and without binders as compared to the commercial charcoal.  In terms of physical characteristics, CMC has showed as an excellent binder with highest shatter index value. Overall, in terms of chemical properties, addition of 10% starch showed a better performance, while addition of 10% CMC showed a better performance in terms of physical characteristics. This finding is beneficial for briquette industry in the development of green product using biomass, but further research is essential before production of briquette take place.